Relasi Kuasa dalam Ondhâgghâ Bhâsa Madhurâ pada Keluarga di Kabupaten Bangkalan dan Kabupaten Sumenep - Kristanti Ayuanita; Masyithah Maghfirah Rizam (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to reveal power relations that are reflected in the use of Madurese language levels or ondhâgghâ bhâsa in families in Bangkalan and Sumenep Regencies. The Madurese language, which has three main levels—enjâ’-iyâ’ (low), èngghi enten (middle), and èngghi bhunten (high)—is used as a tool to signify and maintain social hierarchy within families. This qualitative study employed observation and in-depth interviews with five families from each regency. The findings indicate that the use of èngghi bhunten and èngghi enten in formal situations emphasizes social status differences among family members, while enjâ’-iyâ’ is used in everyday interactions that are more egalitarian, yet still reflect power dynamics, especially between parents and children. The study also reveals a shift in language use, particularly among the younger generation, influenced by modernity and globalization. Overall, ondhâgghâ bhâsa serves not only as a communication tool but also as a mechanism for regulating power relations in Madurese families.